The relevance of international spillovers and asymmetric effects in the Taylor rule - Joscha Beckmann; Ansgar Belke; Christian Dreger (Research On Money in the Economy (ROME), 2014)
Deviations of policy interest rates from the levels implied by the Taylor rule have been persistent before the financial crisis and increased especially after the turn of the century. Compared to the Taylor benchmark, policy rates were often too low. This paper provides evidence that both international spillovers, for instance international dependencies in the interest rate setting of central banks, and nonlinear reaction patterns can offer a more realistic specification of the Taylor rule in the main industrial countries. The inclusion of international spillovers and, even more, nonlinear dynamics improves the explanatory power of standard Taylor reaction functions. Deviations from Taylor rates tend to be smaller and their negative trend can be eliminated.
Keywords: E43; F36; C22; 330; Taylor rule; international spillovers; monetary policy interaction; smooth transition models